PENERJEMAHAN PARTIKEL AKHIR-KALIMAT ZO DALAM BAHASA INDONESIA - Wulandari, Vania Rizky; Aibonotika, Arza; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Sentence-final particle in Japanese called shuujoshi. This study discusses the Japanese sentence-final particle and its equivalent in Indonesian. The particle particles as object to discuss in this study, namely zo. The method used is descriptive qualitative method. A data in this study is collected from reading the conversational dialogues in manga. The results is founding the sentences in manga are indicated using that particles, then has a function called dialogical and non-dialogical. The next of the results, the sentence using zo has an equivalent and non equivalent in Indonesian.Key Words: Sentence-final particle equivalent, Manga, Particle zo